Association of rs10507391 polymorphism with the development of acute cerebrovascular accident in patients with cardiovascular pathology - S. Yu. Nikulina; V. A. Shulman; A. A. Chernova; S. V. Prokopenko; D. A. Nikulin; I. M. Platunova; S. S. Tretyakova; V. N. Chernov; O. V. Marilovtseva; A. N. Kelemeneva; V. N. Maksimov; A. A. Gurazheva (Бюллетень сибирской медицины, 2020)
The aim of the study was to investigatey the association of single-nucleotide polymorphism (SNP) rs10507391 (A>T) with the acute cerebrovascular accident (CVA) development in patients of the East Siberian population with cardiovascular pathology and its risk factors.Material and methods. The study involved 260 patients with acute CVA (age [57.0; 51.0–62.0]) and 272 patients of the control group (age [55.0; 51.0–62.0]). Among the patients who had acute CVA there were 157 men and 103 women. The control group included 170 men and 102 women. The examination of the experimental group included: collection of complaints, anamnesis, clinical examination, computed tomography of the brain, electrocardiography, echocardioscopy, ultrasound duplex scanning of extracranial brachiocephalic arteries, daily blood pressure and heart rate monitoring, and analysis of the blood coagulation system. In patients of the experimental group, the following cardiovascular pathology and risk factors were present: arterial hypertension, paroxysmal supraventricular tachycardias, dyslipidemia, atherosclerosis of the brachiocephalic arteries, and disorders of the hemostatic system. The control group was surveyed in the framework of the international “HAPIEE” project. Molecular genetic research was performed by real-time PCR. Statistical processing of the material was carried out using the following software: Statistica for Windows 7.0, Excel and SPSS 22. Results. When studying the association of SNP rs10507391 (A>T) with the acute CVA development in all the analyzed groups and subgroups of patients, a link was established between the rare TT genotype and the T allele and an increased risk of acute CVA.Conclusion. TT genotype and T allele of the SNP rs10507391 (A>T) increase the risk of acute CVA in patients regardless of previous cardiovascular pathology and its risk factors, including patients with arterial hypertension, supraventricular tachyarrhythmias, atherosclerosis of brachiocephalic arteries, impaired lipid metabolism and hemostasis system.